Gendered success in higher education : global perspectives - White, Kate, 1949 August 3-; O'Connor, Pat, 1950- (Palgrave Macmillan, 2017)
This book examines higher education institutions that exemplify gendered success whether in terms of the presence of women in senior positions or attempts to change a gendered organisational culture. It reflects a global perspective, drawing on case studies from eleven countries: Australia, Austria, Ireland, India, New Zealand, Portugal, South Africa, Sweden, Turkey, United Arab Emirates, and the United Kingdom. In each country an organisation has been selected that demonstrate best practice in terms of gendered outcomes or processes. Gendered Success in Higher Education highlights both the importance and the limitations of indicators such as the proportion of women in senior positions. It proposes a new gender agenda, identifies the factors that need to be included in a model of gendered change, and provides important insights into the nature of gendered change globally and how it can be achieved.- Resumé vydavatel
Keywords: ženy ve školství; vysoké školy; vedoucí pracovnice; gender; women in education; universities and colleges; women managers; elektronické knihy; případové studie; electronic books; case studies